ANALISIS PEMAHAMAN KONSEP IPA BERDASARKAN MOTIVASI BELAJAR, KETERAMPILAN PROSES SAINS, KEMAMPUAN MULTIREPRESENTASI, JENIS KELAMIN, DAN LATAR BELAKANG SEKOLAH MAHASISWA CALON GURU SD - Siti Fatimah (Universitas Negeri Padang, 2017)
Penelitian ini bertujuan untuk menganalisis pemahaman konsep IPA mahasiswa calon guru SD berdasarkan motivasi belajar, keterampilan proses sains, kemampuan multirepresentasi, jenis kelamin, dan latar belakang sekolah. Subyek dalam penelitian ini adalah mahasiswa semester III TA 2016/2017. Analisis pemahaman konsep menggunakan metode CRI. Hasil menunjukkan: 1) Pemahaman konsep IPA dengan kriteria paham konsep sebesar 82,64%, tidak paham konsep sebesar 4,86%, dan miskonsepsi sebesar 12,50%; 2) Pemahaman konsep calon guru SD berdasarkan motivasi belajar kategori tinggi lebih baik daripada yang kategori rendah; 3) Pemahaman konsep calon guru SD berdasarkan keterampilan proses sains kategori tinggi lebih baik daripada yang kategori rendah; 4) Pemahaman konsep calon guru SD berdasarkan kemampuan multirepresentasi kategori tinggi lebih baik daripada yang kategori rendah; 5) Pemahaman konsep calon guru SD perempuan lebih baik daripada laki-laki; 6) Pemahaman konsep calon guru SD yang berasal dari SMA (IPA) lebih baik daripada yang berasal dari SMA (IPS) dan SMK.Kata kunci: Pemahaman Konsep IPA, Motivasi, Kemampuan Multirepresentasi ANALYZING THE UNDERSTANDING OF SCIENCE CONCEPT BASED ON LEARNING MOTIVATION, SCIENCE PROCESS SKILLS, MULTIREPRESENTATION ABILITY, GENDER, AND BACKGROUND OF ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTAbstract This research aims to analyze the students understanding as elementary school teacher candidates about science knowledge concept based on motivation to learn, science process skills, multi-representation ability, gender, and their school background. The subjects in this researcharestudents who are in the third semester of school year 2016/2017. CRI methodology have been used to analyze the understanding of the concept. The result indicates: 1) Understanding about science concept has 82.64 percent of students understand the concept, 4.86 percent of students do not understand the concept, and 12.50 percent of students get misconceptions; 2) Understanding aboutconcept of elementary school teacher candidates based on learning motivation states that the high category better than the low category; 3) Understanding aboutconcept of elementary school teacher candidates based on the science process skills shows that the high category is better than the low category; 4) Understanding aboutconcept of elementary school teachers candidates based on the multi-representations ability indicates that high category is better than the low category; 5) Understanding aboutconcept of the female elementary school teacher candidates is better than the male ones; 6) Understanding aboutconcept of elementary school teacher candidates who have IPA background in the high school is better than those derived from IPS background and vocational high school (SMK).Keywords: Science Concept Understanding, Motivation, Multirepresentation